2021
DOI: 10.1177/03000605211038457
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation: a real-world data analysis on outcomes and differences between rechargeable and non-rechargeable implantable pulse generators

Abstract: Objective In this analysis, we examined differences between rechargeable and non-rechargeable spinal cord stimulation (SCS) devices in patients with pain. Methods We conducted a retrospective, longitudinal claims data analysis using a German research database comprising 5 million statutory insured patients (2012–2017). Outcomes of demographics, patient pathways, and health care resource utilization (HCRU) in patients with initial SCS were collected. Results Of 150 patients in the database, 73 (49%) received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…SCS devices can be distinguished by not only their electrode position but also by how they are powered. 77 The initial SCS devices were powered with external generators, which delivered stimulation. Over time, radiofrequency receivers were implanted subcutaneously to power the devices.…”
Section: Anchoringmentioning
confidence: 99%
See 1 more Smart Citation
“…SCS devices can be distinguished by not only their electrode position but also by how they are powered. 77 The initial SCS devices were powered with external generators, which delivered stimulation. Over time, radiofrequency receivers were implanted subcutaneously to power the devices.…”
Section: Anchoringmentioning
confidence: 99%
“…78 These were not commonly used at first because their cost was higher than nonrechargeable batteries and the idea of charging was off-putting to many patients and physicians. [77][78][79] However, with the advent of smartphones leading to the incorporation of charging into daily routines and the use of SCS waveforms with considerable energy requirements, rechargeable batteries eventually gained popularity. A recent study found that patients spent less than 2 hours a week charging their devices and more than three of four were satisfied with their charging burden.…”
Section: Anchoringmentioning
confidence: 99%
“…11 A recent comparative study by Luecke et al showed patients treated with RC devices have reduced pain diagnoses, hospitalizations, physician visits, and use of pain medications compared to patients treated with NRC devices. 16 In addition to costs and objective outcomes, patient satisfaction with the use of RC or NRC devices is critical for determining how broadly useful these therapies can be for treating patients with chronic pain; however, there has been little published research on this topic. Previous, small surveys of real-world patient cohorts revealed most individuals preferred RC to NRC devices, and the biggest patient-perceived downside to NRC devices was the possibility there could be an extended period without pain relief if implantation of the new IPG was delayed.…”
Section: Introductionmentioning
confidence: 99%
“… 11 A recent comparative study by Luecke et al showed patients treated with RC devices have reduced pain diagnoses, hospitalizations, physician visits, and use of pain medications compared to patients treated with NRC devices. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 18 Despite the growing interest in real-world neuromodulation data, real-world evidence concerning patient selection for SCS in treatment for chronic pain is still limited. 19–22 Within this narrative review, the aim is to provide insights into the indications of SCS for pain in combination with statistical, health-economic, and ethical aspects that may influence the selection of patients for SCS.…”
Section: Introductionmentioning
confidence: 99%